Memory Maintenance and Inhibitory Control Differentiate from Early Childhood to Adolescence - Shing, Yee Lee (2010)
Existing evidence suggests that the organization of cognitive functions may differentiate during development. We investigated two key components of executive functions, memory maintenance and inhibitory control, by applying latent factor models appropriate for examining developmental differences in functional associations among aspects of cognition. Two-hundred and sixty-three children (aged 4 to 14 years) were administered tasks that required maintaining rules in mind or inhibiting a prepotent tendency to respond on the same side as the stimulus. Memory maintenance and inhibitory control were not separable in children of 4–7 or 7–9.5 years, but were differentiated in an older group (9.5–14.5 years).